Power Engineering. Efficiency, Reliability, Safety: Selected Reports of All-Russian Scientific and Technical Conference (London, Red Square, 2014)
Scientific and Technical Conference "Energy: efficiency, reliability, safety" is held annually at the Tomsk Polytechnic University in 1994. Since 2000, it has the All-Russian status. On average, each year at the conference is considered more than 100 reports of scientists, professionals, graduate students and undergraduate students. The Conference is constructed in the following sections:— electricity,— combined heat and power,— nuclear energy,— energy safety and energy efficiency,— ecology energy,— humanitarian problems of energy,— biomedical problems of energy.The Conference became amusing and authoritative scientific and technical activities, which is attended by scientists from most regions of the Russian Federation and foreign countries. Represented in the collection of the reports do not cover the entire breadth and depth of the problems of energy. They aroused a great interest and wide ranging discussion of the Conference participants. The Collection is designed for researchers teachers and professionals and students of universities and enterprises. All observations and recommendations based on the collection of the authors will be greatly appreciated.